GEOPHYSICAL PROSPECTION AT THE FORMATIVE SITE OF ALTICA IN THE TEOTIHUACAN VALLEY PIEDMONT. Issue 2 (2019) - Mejía Ramón, Andrés G.; Barba, Luis; Ortiz, Agustín; Blancas, Jorge
Abstract: The Formative-period site of Altica in the Patlachique Range poses many methodological problems when designing an excavation strategy. Three millennia of erosion, twentieth-century chisel plowing, and modern reforestation efforts have destroyed or disturbed most surface architecture above the local tepetate bedrock. As such, in the early stages of the Altica Project, the primary concern was the detection and identification of subsurface features, especially deep pits as found at other Formative sites. Although Altica is located at the top of a low, flat ridge, strong localized rain frequently flooded the terraces of interest for days, making it impossible to detect subsurface features using the most common prospection techniques. Because of these practical and taphonomic limitations, we relied on magnetic gradient prospection. This technique had never been applied to an early village site in the Basin of Mexico. This paper presents the methods used, discusses various difficulties encountered during prospection, applies interprets the results of the magnetic gradient study using results from excavation and aerial multispectral remote sensing. We discuss how the method might be applied to similar Formative sites to remotely detect indicators of anthropogenic activity, including subsurface features.